Problematika Relasi Pusat-Daerah dalam Implementasi Paradigma Pencegahan yang Berbasiskan Pertahanan Aktif - Muhamad Lukman Arifianto, Muhamad Lukman Arifianto (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to review the meaning of ‘prevention’ and the contestation of its application in the Active Defense scheme contained in the National Action Plan for the Prevention and Eradication of Abuse and Illicit Trafficking of Narcotics (RAN P4GN) and Narcotics Precursors for 2020-2024. The Active Defense-based prevention module requires massive synergies between Government Organizations and Civil Society Organizations that are able to realize a participatory form of collaboration, namely interactive collaboration with community involvement as concentric. However, ‘inequality’ often arises and sinks at the level of policy formulation that should be balanced between central and regional stakeholders. The rigidity of the process of identifying data and information, coupled with the lack of references to academic studies on evidence-based policies regarding the problem of narcotics trafficking and abuse, actually widens the bias in recommendations that seem odd. This paper appears as a response to review and re-examine the contestation of the problematic meaning of Prevention in the P4GN design through the perspective of the theory of change.